Skin manifestations in young military personnel diagnosed with Covid 19 - Peru - Febres Ramos, Richard Jeremy (2020)
COVID-19 is a highly contagious respiratory tract infection caused by severe acute respiratory syndrome coronavirus 2. The infection has been reported to demonstrate different types of skin manifestations including urticarial, maculopapular, papulovesicular, purpuric, livedoid, and thrombotic-ischemic lesions. Given the high mortality rate of the infection, timely and accurate identification of relevant skin manifestations can play a key role in early diagnosis and management.Skin manifestations, a well-known effect of viral infections, are beginning to be reported in patients with COVID-19 disease. These manifestations most often are morbilliform rash, hives, vesicular rashes, acral lesions, and livedoid rashes. Some of these skin manifestations arise before the signs and symptoms most commonly associated with COVID-19, suggesting that they may be showing signs of COVID-19 Bibliographic reports showed great heterogeneity in the skin manifestations associated with COVID-19, as well as in their latency periods and associated extracutaneous symptoms. Pathogenic mechanisms are unknown, although the functions of an overactive immune response, complement activation and microvascular injury have been hypothesized. Based on our experience and bibliographic data, we subdivide reported skin lesions into six main clinical patterns: (I) urticarial rash; (II) erythematous-maculopapular-morbilliforma confluent rash; (III) papulovesicular exanthemum; (IV) chilblain-like acral pattern; (V) livedo reticularis–livedo racemosa-like pattern; and (VI) purpurico "vasculytic" pattern. These six patterns can be fused into two main groups: the first – inflammatory and exanthemum – includes the first three groups mentioned above, and the second includes vasculopathic and vasculytic lesions of the last three groups.We can conclude that skin manifestations are similar to skin involvement that occurs during common viral infections.